Emphysematous Pyelonephritis—a Rare Surgical Emergency Presenting to the Physician: A Case Report and Literature Review - Saxena, Divish (Springer India, 2012)
Emphysematous pyelonephritis is an acute necrotizing parenchymal and perirenal infection caused by gas-forming uropathogens. It is a rare condition, usually occurring in diabetic patients. Mortality rates in medically managed patients are as high as 70–90 %. It should be suspected in diabetic patients with urinary tract infections and worsening of renal function. CT scan is diagnostic and is the method of choice for diagnosis and follow-up. Both physicians and surgeons should be aware of this rare condition which might present to the physician as fulminant urinary tract infection in an uncontrolled diabetic patient, but which might warrant urgent surgical intervention by way of an emergency nephrectomy. We report a 60-year-old diabetic woman who presented with urinary infection and sepsis. Initially she was managed conservatively, but had to be taken up for emergency nephrectomy in view of her worsening condition. We review the clinical presentation, radiological diagnosis with characteristic CT scan pictures, and the management of this rare condition.